2020
DOI: 10.3390/ijms21082722
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Altered Adipose Stem Cells Promote Radiation Resistance of Estrogen Receptor Positive Breast Cancer through Paracrine Signaling

Abstract: R.A.S.); vvillela@tulane.edu (V.A.V.); acote1@lsuhsc.edu (A.D.); rwise@tulane.edu (R.M.W.); mharri26@tulane.edu (M.A.A.H.); msandle1@tulane.edu (M.B.S.)Abstract: Obesity is associated with poorer responses to chemo-and radiation therapy for breast cancer, which leads to higher mortality rates for obese women who develop breast cancer. Adipose stem cells (ASCs) are an integral stromal component of the tumor microenvironment (TME). In this study, the effects of obesity-altered ASCs (obASCs) on estrogen receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…It is secreted by adipocytes and it signals to the brain to inhibit food intake, and thus, help in decreasing weight (Ahima, 2008). So far, the idea of leptin as an anti‐obesity hormone was not clear because obesity is characteristically related to high leptin levels but not to leptin deficiency (Flier, 1998; Heymsfield et al., 1999; Sabol et al., 2020). In this study, we observed the selective downregulation of serum leptin levels in HFO which was supported by the existing literature published by many researchers (Flier, 1998; Gray, Steyn, Davies, & Vitetta, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted by adipocytes and it signals to the brain to inhibit food intake, and thus, help in decreasing weight (Ahima, 2008). So far, the idea of leptin as an anti‐obesity hormone was not clear because obesity is characteristically related to high leptin levels but not to leptin deficiency (Flier, 1998; Heymsfield et al., 1999; Sabol et al., 2020). In this study, we observed the selective downregulation of serum leptin levels in HFO which was supported by the existing literature published by many researchers (Flier, 1998; Gray, Steyn, Davies, & Vitetta, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it may stimulate the epithelial mesenchymal transition (EMT) (80), which has been confirmed to activate the EMT of breast cancer cells by upregulating pyruvate kinase M2 to activate the PI3K/ Akt pathway (81), increasing the activity of matrix metalloproteinases (MMPs), promoting the formation and maintenance of breast cancer stem cell (BCSC) survival, inducing the activation and proliferation of endothelial cells and modulating tumor-immune cell cross talk. Sabol et al (82) found through molecular experiments that adipose stem cells modified by obesity promoted the secretion of leptin and upregulated and activated the IL-6 and Notch signaling pathways in ER+ breast cancer cells, resulting in ER+ breast cancer radiation resistance. Leptin signaling affects the progression of ER-breast cancer (83).…”
Section: Leptinmentioning
confidence: 99%
“…Human female, subcutaneous, abdominal ASCs were obtained from LaCell LLC/Obatala Sciences Inc. (New Orleans, LA, USA). Individual ASC cell lines were previously fully characterized by our laboratory prior to being pooled [ 25 , 26 , 44 , 45 , 46 ]. Following pooling an abbreviated characterization was completed to ensure expression of basic stemness characteristics.…”
Section: Methodsmentioning
confidence: 99%